2021
DOI: 10.1186/s12960-020-00549-w
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional education and collaborative practice policies and law: an international review and reflective questions

Abstract: Background Healthcare is a complex sociolegal setting due to the number of policymakers, levels of governance and importance of policy interdependence. As a desirable care approach, collaborative practice (referred to as interprofessional education and collaborative practice (IPECP)) is influenced by this complex policy environment from the beginning of professionals’ education to their initiation of practice in healthcare settings. Main body Altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 56 publications
0
3
0
1
Order By: Relevance
“…The authors identified IPE as a necessity to strengthen and enhance students' competencies of acupuncture knowledge and skills. Girard (2021) and Müller and Couper (2021) agree that IPE is an effective means to optimise patient care by promoting students' competencies in clinical practice through knowledge and understanding from different professionals in the field. Despite scholars contending on the importance of IPE, the Presidential Advisory Council on Combating Antibiotic-Resistant Bacteria (PACCARB) (2021) points out that there is a lack of a shared vision of an educational framework for IPE.…”
Section: Background To Acupuncture and Interprofessional Educationmentioning
confidence: 99%
“…The authors identified IPE as a necessity to strengthen and enhance students' competencies of acupuncture knowledge and skills. Girard (2021) and Müller and Couper (2021) agree that IPE is an effective means to optimise patient care by promoting students' competencies in clinical practice through knowledge and understanding from different professionals in the field. Despite scholars contending on the importance of IPE, the Presidential Advisory Council on Combating Antibiotic-Resistant Bacteria (PACCARB) (2021) points out that there is a lack of a shared vision of an educational framework for IPE.…”
Section: Background To Acupuncture and Interprofessional Educationmentioning
confidence: 99%
“…How IPE is conceptualized and practiced can vary depending on the country and the healthcare setting. Further to this, regulations on interprofessional competencies vary across countries (8,9). Despite this variability, some commonly described themes and elements include effective communication, mutual respect, teamwork, reflexive practice, leadership and management, and ethical considerations (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] A growing body of knowledge describes the adoption, development, and evaluation of IPE initiatives globally. [3,4] Moreover, several countries now require all undergraduate health professions students to provide evidence of IPE at graduation. [5] These IPE initiatives appear to be aligned with the "Framework of Action" proposed by the World Health Organization (WHO) that recommends IPE as a strategy to catalyze collaborative practice through the development of four key competencies, namely values and ethics, roles, and responsibilities, interprofessional communication and teamwork.…”
Section: Introductionmentioning
confidence: 99%